'Man MOT': a new approach to primary care for men. Issue 1 (January 2017) - Baker, Peter
Abstract : Men find it difficult to make effective use of primary care. Peter Baker describes a successful new service that provides online GP chat and advice for men, and the lessons that can be learned from it.